Arthroscopic Arthrodesis of the Lesser Ray Tarsometatarsal Joints: 2-Portal Technique - Tun Hing Lui, M.B.B.S.(H.K.), F.R.C.S.(Edin.), F.H.K.A.M., F.H.K.C.O.S. (Arthroscopy Techniques, 2017)
Tarsometatarsal (Lisfranc) destruction of the tarsometatarsal articulation of the lesser rays is most commonly due to midfoot Charcot neuroarthropathy. Tarsometatarsal arthrodesis is indicated when conservative management cannot relieve the symptoms. The purpose of this Technical Note is to describe a minimally invasive approach of arthroscopic arthrodesis of the destructed lesser ray tarsometatarsal joints. The arthroscopic procedure is performed through the lateral and P1-2 Lisfranc portals. It has the advantages of better cosmesis, less wound complication, less bone resection, and more thorough joint debridement. However, it is contraindicated if there is associated significant foot deformity or shortening of the lesser foot rays.